International development - Seth Appiah-Opoku (International development, 2017)
This book brings together leading researchers in the field of international development to examine issues relating to food security, health, rural development, human development, and institutional strengthening in developing countries. Based on empirical research, the book discusses a variety of topics including nutrition-sensitive agricultural development in South Africa, household food security in Tanzania, medical research in Egypt, child mortality in Christian and Islamic countries, spot improvement of rural roads in Asia and Africa, resilience in natural disaster, the relationship between foreign aid and human development in Africa, and finally developing competencies for rural development project management through the creation of local action groups in Argentina. The book is insightful and serves as an important reference material on international development.
10.5772/63034; 10.5772/63034